The Arab uprisings : what everyone needs to know - Gelvin, James L., 1951- (Oxford University Press, 2012)
Beginning in December 2010 popular revolt swept through the Middle East, shocking the world and ushering in a period of unprecedented unrest. Protestors took to the streets to demand greater freedom, democracy, human rights, social justice, and regime change. What caused these uprisings? What is their significance? And what are their likely consequences? In an engaging question-and-answer format, The Arab Uprisings explores all aspects of the revolutionary protests that have rocked the Middle East. Historian James Gelvin begins with an overview--What sparked the Arab uprisings? Where did the d
Description based upon print version of record.
Keywords: Protest movements -- Arab countries -- History -- 21st century.; Protest movements -- Middle East -- History -- 21st century.; Protest movements -- Middle East.; Arab countries -- Politics and government -- 21st century.; Middle East -- Politics and government -- 21st century.